Designing and implementing maker curriculum for promoting 7th graders’ maker competence - Wu, Su-Chiao; Chang, Yu-Liang (Frontiers in Education, 2023)
“Competence” is a very important concept in education and has been valued by several countries and international organizations in recent years, sparking a wave of curriculum reforms worldwide. The STEAM education is considered a feasible way to equip all students with problem-solving skills in various real-world situations and complicated challenges, as well as nurturing them 21st century skills and competencies. Moreover, a recent maker movement that focuses more on hands-on creation, design, and innovation is considered an innovative way to redefine the learning process through which students’ maker competence can be nurtured. Based on this trend, new national curriculum guidelines were established by Taiwan’s Ministry of Education in 2014. Particularly for the technology domain in the junior high school level (grade 7–9), “Life Technology” and “Information Technology” become requirements, where an interdisciplinary and competence-based maker curriculum needs to be developed. Based on this curriculum reform wave, we emphasize for the implementation of a targeted maker curriculum as a way to increase 7th-grade students’ maker competence. A post-test quasi-experimental design was employed to gather the data, and corresponding statistics were applied for quantitative comparison. A total of 230 7th-graders from eight classes in the targeted junior high schools participated in this study. Students in the experimental group received an interdisciplinary and competence-based maker curriculum as the intervention, which was designed and implemented with the support of the teacher professional development community and briefly presented in this paper. The quantitative findings revealed that the 7th-graders who received the experimental intervention possessed significantly superior marker competence compared to those who received regular technology courses. Based on these findings, maker competence (i.e., knowledge, attitude, and skills), which can be fully established within interdisciplinary and competence-based maker classrooms, was significantly favorable for helping targeted adolescents survive in this ever-changing and fast-paced era. Consequently, as teacher educators and teachers, we must endeavor to redefine the way of learning and construct a learning environment that is full of the maker spirit and STEAM integration.